Sustainable public procurement: realization of the social aspect in republic of Lithuania - Kanapinskas, Virginijus; Plytnikas, Žydrūnas; Tvaronavičienė, Agnė (Business: Theory and Practice, 2014)
Public procurement concentrates large public sector’s purchasing power, and has a significant impact on each country’s economic development. The purpose of public procurement procedure is transparency, non-discrimination and accordance to the principles of fair competition in acquisition of goods, services and works necessary for the smooth functioning of the public administration. Besides, public procurement can be one of the most important instruments for sustainable development and other purposes useful to the whole society and the economy of the country. This article briefly discusses the concept of sustainable public procurement, reveals its main ideas and applications. One of them, the social sphere, was chosen the main object of the research. The possibility to decrease unemployment, to increase an integration of socially vulnerable group, and to achieve other socially-oriented goals through an effective implementation of the social aspect of sustainable public procurement has been illustrated. Thus, the article analyses the concept of social procurement, assesses the current situation in Lithuania, overviews the good practice of other countries and provides recommendations for measures to extend the application of socially oriented procurement.